Game-Based Learning untuk Numerasi Arab: Desain dan Implementasi Media Ular Tangga di Madrasah Tsanawiyah Negeri - Putri Eka May Zura Dani; Muflihah Muflihah (EduInovasi: Journal of Basic Educational Studies, 2025)
Arabic language learning at the madrasah level still faces challenges, particularly in mastering numerical material among students. The lack of interactive and engaging media causes learners to be less motivated and to struggle with memorizing and using numbers in Arabic. This study aims to describe the implementation of the Snakes and Ladders game as an instructional medium in teaching Arabic numerals and to measure its effectiveness on students’ comprehension and learning motivation. The research subjects were 32 students of class 7B at MTs Negeri 2 Lamongan. The study employed a descriptive qualitative method with a participatory approach, involving stages of direct instruction, observation, documentation, and learning outcome evaluation. The Snakes and Ladders medium was contextually developed to include Arabic numbers from 1 to 100 and was played collaboratively in groups. The findings revealed that the application of this medium successfully created an active, enjoyable, and collaborative learning environment. Students showed improvements in recognizing and pronouncing Arabic numbers and demonstrated greater enthusiasm in class participation. The use of the Snakes and Ladders game in Arabic numeracy learning proved effective in enhancing students’ motivation, active participation, and understanding compared to conventional methods.